Plasma Plasmodium falciparum Histidine-rich Protein 2 Concentrations in Children With Malaria Infections of Differing Severity in Kilifi, Kenya. (9th August 2020) - Uyoga, Sophie; Wanjiku, Perpetual; Rop, Jesse C; Makale, Johnstone; Macharia, Alexander W; Nyutu, Gideon M; Shebe, Mohammed; Awuondo, Kennedy A; Mturi, Neema; Woodrow, Charles J; Dondorp, Arjen M; Maitland, Kathryn; et al.
Abstract: Background: Most previous studies support a direct link between total parasite load and the clinical severity of Plasmodium falciparum malaria infections. Methods: We estimated P. falciparum parasite loads in 3 groups of children with malaria infections of differing severity: (1) children with World Health Organization–defined severe malaria (n = 1544), (2) children admitted with malaria but without features of severity (n = 200), and (3) children in the community with asymptomatic parasitemia (n = 33). Results: Peripheral parasitemias were highest in those with uncomplicated malaria (geometric mean [GM] parasite count, 111 064/μL; 95% confidence interval, CI, 86 798–141 819/μL), almost 3 times higher than in those with severe malaria (39 588/μL; 34 990–44 791/μL) and >100 times higher than in those with asymptomatic malaria (1092/μL; 523–2280/μL). However, the GM P. falciparum histidine-rich protein 2 ( Pf HRP2) values (95% CI) increased with severity, being 7 (4–12) ng/mL in asymptomatic malaria, 843 (655–1084) ng/mL in uncomplicated malaria, and 1369 (1244–1506) ng/mL in severe malaria. Pf HRP2 concentrations were markedly lower in the subgroup of patients with severe malaria and concomitant invasive bacterial infections of blood or cerebrospinal fluid (GM concentration, 312 ng/mL; 95% CI, 175–557 ng/mL; P < .001) than in those without such infections (1439 ng/mL; 1307–1584; P < .001). Conclusions: The clinical severity of malaria infections related strongly to the total burden of P. falciparum parasites. A quantitative test for plasma concentrations of Pf HRP2 could be useful in identifying children at the greatest clinical risk and identifying critically ill children in whom malaria is not the primary cause. Abstract : Through a clinical surveillance study, we show that plasma levels of Plasmodium falciparum histidine-rich protein 2, a marker of total body parasite load, are strongly correlated with the severity of P. falciparum infections among children in Kilifi, Kenya.